2021
DOI: 10.3390/s21072480
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Low-Drift Inertial Sensor-Based System for Analysis of Alpine Skiing Performance

Abstract: In skiing it is important to know how the skier accelerates and inclines the skis during the turn to avoid injuries and improve technique. The purpose of this pilot study with three participants was to develop and evaluate a compact, wireless, and low-cost system for detecting the inclination and acceleration of skis in the field based on inertial measurement units (IMU). To that end, a commercial IMU board was placed on each ski behind the skier boot. With the use of an attitude and heading reference system a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…The youth group is fundamental. Carvajal [16] analysed the participation of the masses in winter sports in different regions and found that outdoor winter sports were dominated by young people and people above the middle class, with more men than women. Schools organised the main outdoor exercises of students in winter.…”
Section: Related Workmentioning
confidence: 99%
“…The youth group is fundamental. Carvajal [16] analysed the participation of the masses in winter sports in different regions and found that outdoor winter sports were dominated by young people and people above the middle class, with more men than women. Schools organised the main outdoor exercises of students in winter.…”
Section: Related Workmentioning
confidence: 99%
“…The utilization of wearables, as previously outlined, allows individuals to emotionally connect with the technology and product due to personal interest [10], which is seen as key to the adoption of new technologies [21]. Sports using wearables include snowboarding [20], athletics and the biomechanics of running [22], cross-country skiing [23] and team-based sports [24]. Of these, running, walking, and jumping, which are the primary means of locomotion and enablers for many physical activities, were seen as the most natural 'first base' for technol-ogy translation into an educational tool such as the STEMfit software package [25].…”
Section: Wearable Technology Designmentioning
confidence: 99%
“…IMU-based systems have been extensively characterized in relation to human motion analyses and have gained applicability in numerous fields, including posturography [ 36 , 37 , 38 ], sports [ 39 , 40 , 41 ], and clinical practice [ 42 , 43 , 44 ]. While the use of IMU systems in equine science is less documented, we hypothesize that they represent practical tools for equine clinicians and researchers alike.…”
Section: Introductionmentioning
confidence: 99%